Patients With Coronavirus Disease 2019 Requiring Invasive Mechanical Ventilation in Mexico in the First, Second, and Exponential Growth Phase of the Third Wave of the Coronavirus Disease 2019 Pandemic - Silvio A. Ñamendys-Silva, MD, MSc, FCCP, FCCM (Wolters Kluwer, 2021)
A total of 3,197,108 coronavirus disease 2019 cases (2,537 cases per 100,000 people) and 252,080 deaths (200 deaths per 100,000 people) were recorded in Mexico as of August 20, 2021. There were 36,934 of 203,582 coronavirus disease 2019 patients (18.1%) that required invasive mechanical ventilation during the first wave of coronavirus disease 2019, 24,698 of 253,899 (9.7%) patients during the second wave, and 5,610 of 65,952 (8.5%) during the exponential growth phase of the third wave (p < 0.001). The proportion of patients who received invasive mechanical ventilation in the ICU was lower in the first wave (27.9%) and then remained between 33.3% and 36.2% for the remainder of that period. Although the inhospital mortality of hospitalized coronavirus disease 2019 patients requiring intubation during the exponential growth phase of the third wave was lower than that in the first and second waves, the inhospital mortality in coronavirus disease 2019 patients requiring invasive mechanical ventilation remained greater than 82%.